Determinants of work-related skin symptons and dermatitis associated with cleaning agents among health workers of two tertiary hospitals in Southern Africa - Sonday, Zahida (Department of Public Health and Family Medicine, 2024)
Background: Cleaning products and related agents are increasingly associated with occupational irritant and allergic contact dermatitis in health workers (HWs), but limited information is available on predictors for these outcomes. This study investigated the prevalence and risk factors for work-related skin symptoms (WRSS) and skin disease phenotypes in HWs exposed to diverse cleaning agents in two Southern African tertiary hospitals. Methods: A cross-sectional study of 697 HWs used an interviewer administered questionnaire and assessed the presence of atopy using Phadiatop. Results: The median age of HWs was 42 years (IQR: 32 – 51), 77.0% were female and 42.5% were atopic. The lifetime prevalence of WRSS was 18.7% and WRSS in the last 12 months was slightly lower (14.8%). Among the skin disease phenotypes, 12.3% had probable contact dermatitis and 3.2% probable contact urticaria. In multivariate regression models, adjusted for family history of allergy and domestic cleaning frequency, technicians (ORadj 4.45, 95% CI: 1.21-21.48) and work activities involving cleaning and disinfection of skin wounds (ORadj 2.70, 95% CI: 1.64-4.57) was associated with WRSS in the past year. A consistent trend was observed for job tasks and cleaning agents related to these work activities. Risk factors for probable contact dermatitis included the use of liquid hand soap (ORadj 1.67, 95% CI: 1.03- 2.72), sterilising instruments manually (ORadj 1.94, 95% CI: 1.15-3.19) or automatically (ORadj 3.28, 95% CI: 1.01-9.32), disinfecting skin prior to procedures (ORadj 2.29, 95% CI: 1.45-3.66) and the use of adhesives for wounds (ORadj 1.91, 95% CI: 1.20-3.07). Risk factors for probable contact urticaria included specimen preparation (ORadj 2.65, 95% CI: 1.06-6.38) and wound cleaning and disinfection (ORadj 3.10, 95% CI: 1.24-8.81). Training on protection against adverse health effects of cleaning agents (ORadj 0.54, 95% CI: 0.31-0.89) was protective against WRSS in the past year. Conclusion: Workplace activities and related factors associated with cleaning and disinfecting of patients' skin and wounds are important risk factors for WRSS in HWs. Training on the adverse health effects of cleaning agents can contribute to decreasing risks in HWs. Keywords: health workers, skin symptoms, cleaning agents